2022
DOI: 10.1186/s12874-022-01544-6
|View full text |Cite
|
Sign up to set email alerts
|

Individual-specific networks for prediction modelling – A scoping review of methods

Abstract: Background Recent advances in biotechnology enable the acquisition of high-dimensional data on individuals, posing challenges for prediction models which traditionally use covariates such as clinical patient characteristics. Alternative forms of covariate representations for the features derived from these modern data modalities should be considered that can utilize their intrinsic interconnection. The connectivity information between these features can be represented as an individual-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 116 publications
0
10
0
Order By: Relevance
“…Many neuroimaging studies have demonstrated the potential of functional network connectivity patterns estimated from rs-fMRI to discriminate groups or to predict a clinical outcome. 17 Two modeling approaches are mainly employed in applied studies to address the variability of graph-theoretical features resulting from the selection of thresholds across a broad spectrum of sparsity levels. The first one selects a single threshold based on optimal prediction (OPT), while the other one averages the resulting graph-theoretical feature over a predefined range of thresholds (AVG).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many neuroimaging studies have demonstrated the potential of functional network connectivity patterns estimated from rs-fMRI to discriminate groups or to predict a clinical outcome. 17 Two modeling approaches are mainly employed in applied studies to address the variability of graph-theoretical features resulting from the selection of thresholds across a broad spectrum of sparsity levels. The first one selects a single threshold based on optimal prediction (OPT), while the other one averages the resulting graph-theoretical feature over a predefined range of thresholds (AVG).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, it is either a maximum value for the density (density-based thresholding) or a minimum edge weight (weight-based thresholding). 17 Approaches to sparsify the individual-specific networks are not tied to the specific method used to estimate the connection strength. Neither for density-based nor for weight-based thresholding is there a commonly accepted consensus on the exact threshold that should be used to infer the individual-specific networks A i , and various methods are used in practice to determine the threshold at which graph-theoretical characteristics become relevant for prediction.…”
Section: Concepts Of Graph Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Common practice is to aggregate information, such as averaging edge weights in each ISN, and then look for associations with phenotypes of interest (for instance, drug reaction and time-to-clinical-event 22 , 23 ). The most common objective of studies that include ISNs as input is prediction (for a review, see 24 ). This usually involves extracting graph-theoretical features and linking them to a phenotype of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the graph analyses for complex diseases aggregate information across a whole cohort, failing to detect individual characteristics [ 5 ]. Exploiting individual-specific interactions rather than population-level systems will capture the heterogeneity between individuals and enhance the identification of new biomarkers for precision medicine.…”
Section: Introductionmentioning
confidence: 99%